Auxin biosynthesis maintains embryo identity and growth during BABY BOOM-induced somatic embryogenesis. Issue 2 (1st December 2021) - Li, Mengfan; Wrobel-Marek, Justyna; Heidmann, Iris; Horstman, Anneke; Chen, Baojian; Reis, Ricardo; Angenent, Gerco C; Boutilier, Kim
Abstract: Somatic embryogenesis is a type of plant cell totipotency where embryos develop from nonreproductive (vegetative) cells without fertilization. Somatic embryogenesis can be induced in vitro by auxins, and by ectopic expression of embryo-expressed transcription factors like the BABY BOOM (BBM) AINTEGUMENTA-LIKE APETALA2/ETHYLENE RESPONSE FACTOR domain protein. These different pathways are thought to converge to promote auxin response and biosynthesis, but the specific roles of the endogenous auxin pathway in somatic embryogenesis induction have not been well-characterized. Here we show that BBM transcriptionally regulates the YUCCA3 ( YUC3 ) and YUC8 auxin biosynthesis genes during BBM-mediated somatic embryogenesis in Arabidopsis ( Arabidopsis thaliana ) seedlings. BBM induced local and ectopic YUC3 and YUC8 expression in seedlings, which coincided with increased DR5 auxin response and indole-3-acetic acid (IAA) biosynthesis and with ectopic expression of the WOX2 embryo reporter. YUC-driven auxin biosynthesis was required for BBM-mediated somatic embryogenesis, as the number of embryogenic explants was reduced by ca. 50% in yuc3 yuc8 mutants and abolished after chemical inhibition of YUC enzyme activity. However, a detailed YUC inhibitor time-course study revealed that YUC-dependent IAA biosynthesis is not required for the re-initiation of totipotent cell identity in seedlings. Rather, YUC enzymes are required later in somatic embryo development for the maintenance of embryo identity and growth. This study resolves a long-standing question about the role of endogenous auxin biosynthesis in transcription factor-mediated somatic embryogenesis and also provides an experimental framework for understanding the role of endogenous auxin biosynthesis in other in planta and in vitro embryogenesis systems. Abstract : The BABY BOOM transcription factor induces YUCCA-dependent auxin biosynthesis during somatic embryogenesis to maintain embryo identity and development.